2017
DOI: 10.1097/mpg.0000000000001376
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Inflammation May Influence Liver Stiffness Measurements by Transient Elastography in Children and Young Adults

Abstract: Objectives Transient elastography (TE) measures liver stiffness to assess fibrosis. Studies in adults have shown that inflammation increases stiffness, leading to an overestimation of fibrosis. We investigated the contribution of inflammation to liver stiffness measurements (LSM) in children/young adults. Methods This was a cohort analysis of children/young adults who underwent TE within 1 year of liver biopsy. ALT was obtained within 30d of the biopsy and LSM. Fibrosis was assessed by METAVIR stage and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
0
37
2
Order By: Relevance
“…Previously determined cutoffs for cirrhosis at the time of PE are slightly lower compared to our results . Because histologic inflammation and cholestasis are prominent at PE and both may influence liver stiffness, results obtained at the time of initial surgery are not directly comparable to the postoperative period after COJ. Further, the published BALF score based on albumin, GGT, and bilirubin reflecting follow‐up fibrosis stage in an unselected sample of patients with BA showed no diagnostic accuracy in our cohort comprising solely patients with successful PE .…”
Section: Discussioncontrasting
confidence: 96%
“…Previously determined cutoffs for cirrhosis at the time of PE are slightly lower compared to our results . Because histologic inflammation and cholestasis are prominent at PE and both may influence liver stiffness, results obtained at the time of initial surgery are not directly comparable to the postoperative period after COJ. Further, the published BALF score based on albumin, GGT, and bilirubin reflecting follow‐up fibrosis stage in an unselected sample of patients with BA showed no diagnostic accuracy in our cohort comprising solely patients with successful PE .…”
Section: Discussioncontrasting
confidence: 96%
“…103 However, another paediatric study showed that the presence of liver inflammation might overestimate the liver stiffness measurement by TE in children with early fibrosis stages. 104 One of the most sensitive techniques in children is magnetic resonance (MR)-based techniques. Regarding hepatic steatosis quantification, MR-spectroscopy-proton density fat fraction (MRS-PDFF) and MRI-PDFF have shown to be very accurate and reliable methods in children.…”
Section: Imagingmentioning
confidence: 99%
“…However, with more advanced fibrosis, inflammation did not appear to contribute to LSM. Caution must be taken when interpreting LSM for assessing fibrosis severity in the setting of inflammation [11].…”
Section: Correlation With Fibrosis Stage and Different Etiologiesmentioning
confidence: 99%